Influence on emergency digit replantation and outcome assessment after COVID-19 virus nucleic acid testing normalization - Zhang, Kunqi; Zhang, Rui; Li, Shanyu; Liu, Shenghe; Wang, Feiyan; Xu, Jia; Kang, Qinglin (Frontiers in Surgery, 2023)
Objective To compare the implementation and prognosis of emergency digit replantation surgery before and after normalized COVID-19 nucleic acid testing for patients taking emergency operation, and to explore the influence of normalized COVID-19 nucleic acid testing on replantation surgery. Method Normalized COVID-19 nucleic acid testing for patients taking emergency operation has been carried out since 1st August, 2021 at our hospital, which means each patient who needs emergency surgical treatment has to obtain either positive or negative results of COVID-19 nucleic acid before entering the operating room. This research reviewed and compared the prognosis of the injured extremity which took emergency severed digit replantation between June, 2021 and September, 2021, at Shanghai Jiao Tong University Affiliated Sixth People’s Hospital, and analyzed the impact of normalized COVID-19 nucleic acid testing on the outcome of the replanted fingers of different severity using DASH and HISS scoring system. Results A total of 54 cases with 74 severed replanted phalanges were included replanted by the research group between 1st August, 2021 and 30th September, 2021, without any COVID-19 suspected/confirmed case detected. Compared with previous period (1st June, 2021 to 31st July, 2021), although the interval between emergency visits and emergency replantation did increase significantly after normalized COVID-19 nucleic acid testing [(3.83 ± 0.94)h to(1.77 ± 0.67)h, P<0.05], we observed no significant difference in the improvement rate of DASH the scoring of the disabled upper extremity 3-month postoperatively (P=0.538), nor was seen in the complication rate (P=0.344). Besides, there was no significant difference in the improvement rate of the DASH scoring of the disabled upper extremity 3-month postoperatively in patients with different traumatic severity before and after normalized COVID-19 nucleic acid testing (Moderate P=0.269, Severe P=0.055, Major P=0.149). Conclusion Despite of the preoperative delay, the policy of COVID-19 nucleic acid testing normalization does not have explicit influence on the short-term outcomes of emergency digit replantation surgery. With this evidence, microsurgeons could pay attention to the patients’ anxiety and spend more effort in comforting them during the prolonged preoperative wait. These insights may have implications for other emergency department resource management whenever a social crisis occurs.